A Comparative Study on the Effectiveness of Azotobacter chroococcum and Beijerinckia indica as Biofertilizers for Enhancing the Growth of Alternanthera ficoidea - Dwi Nur Rikhma Sari (Journal of Biotropical Research and Nature Technology, 2025)
The increasing global demand for food has driven the development of environmentally friendly technologies in agriculture, one of which involves the use of nitrogen-fixing bacteria-based biofertilizers. This study aims to evaluate the effectiveness of two nitrogen-fixing bacterial species, Azotobacter chroococcum and Beijerinckia indica, in enhancing the growth of red spinach (Alternanthera ficoidea) in acidic soil conditions. The results revealed that treatments with various concentrations of bacterial inoculants did not have a statistically significant effect on plant height, based on a two-way ANOVA test (α > 0.05). However, descriptively, B. indica demonstrated more optimal performance compared to A. chroococcum and their combination, particularly at a concentration of 15 mL, which produced the highest plant height (31.00 cm). B. indica exhibited better survival and functionality in acidic soil (pH 4–4.5), whereas A. chroococcum was less efficient under such conditions. These findings underscore the importance of selecting bacterial strains that are compatible with specific soil characteristics to enhance the efficacy of biofertilizers and support the growth of ornamental plants such as A. ficoidea.